MENINGKATKAN KREATIVITAS PESERTA DIDIK PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS PROYEK DI SMP NEGERI 1 KEDUNGWUNI: Pembelajaran Proyek, Pendidikan Agama Islam, Kreativitas - Gunawan, Najib; Nesy Septiani; M. Syahrul Aziz (Jurnal Pengabdian Kepada Masyarakat Patikala, 2024)
Education is the main key in producing a quality young generation. One effective approach in education is the use of learning methods that are centered on skills and focus on the needs and potential of students. Learning Islamic Religious Education (PAI) at the Junior High School (SMP) level is one of the significant efforts in shaping the character and spiritual knowledge of students. At SMP Negeri 1 Kedungwuni, project-based learning methods have been implemented, one of which is through the creation of a mading (wall magazine) as part of the learning process. This project-based learning approach aims to improve the quality and creativity of students. In the context of PAI, the project being worked on focuses on the material of Asmaul Husana, where students are given the freedom to express their ideas and creativity in the form of a mading. This community service activity uses a qualitative descriptive method to understand and describe the process and results of implementing this method. The results of this community service activity show that all students are able to actively participate in the mading project. They managed to express their ideas and creativity collaboratively according to the agreement in the group. This process not only helps students understand the PAI material better, but also improves their ability to work together and think creatively. This project-based learning, with a focus on practical skills such as making wall magazines, has proven effective in encouraging active participation and developing students' potential at SMP Negeri 1 Kedungwuni.